2023
DOI: 10.1002/ange.202301331
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Fusion of Thermoresponsive Polypeptides with UCST‐type Behavior Mediates 1D Assembly of Coiled‐Coil Bundlemers

Abstract: Thermoresponsive resilin-like polypeptides (RLPs) of various lengths were genetically fused to two different computationally designed coiled coil-forming peptides with distinct thermal stability, to develop new strategies to assemble coiled coil peptides via temperature-triggered phase separation of the RLP units. Their successful production in bacterial expression hosts was verified via gel electrophoresis, mass spectrometry, and amino acid analysis. Circular dichroism (CD) spectroscopy, ultraviolet-visible (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…They demonstrated that the coacervation of the RLPs upon cooling below their UCST combined with the propensity of the rigid, orderpromoting peptides to remain intact enables control over nanofibrillar (1D) self-assembly. 33 Stimuli-responsive triblock copolypeptides composed of ELPs and ligand-responsive calmodulin (CalM) having helical structure have also been recombinantly synthesized. 34 Upon heating dilute solutions of ELP-CalM-ELP above the T t , these triblock copolypeptides self-assemble into nanoscale vesicles with diameters of ∼240−455 nm, depending on salt-and ligand-induced conformational changes of the middle CalM blocks.…”
Section: Synidps Fused To Helicesmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that the coacervation of the RLPs upon cooling below their UCST combined with the propensity of the rigid, orderpromoting peptides to remain intact enables control over nanofibrillar (1D) self-assembly. 33 Stimuli-responsive triblock copolypeptides composed of ELPs and ligand-responsive calmodulin (CalM) having helical structure have also been recombinantly synthesized. 34 Upon heating dilute solutions of ELP-CalM-ELP above the T t , these triblock copolypeptides self-assemble into nanoscale vesicles with diameters of ∼240−455 nm, depending on salt-and ligand-induced conformational changes of the middle CalM blocks.…”
Section: Synidps Fused To Helicesmentioning
confidence: 99%
“…The Kiick group also functionalized RLPs with computationally designed coiled-coil-forming peptides. They demonstrated that the coacervation of the RLPs upon cooling below their UCST combined with the propensity of the rigid, order-promoting peptides to remain intact enables control over nanofibrillar (1D) self-assembly …”
Section: Synidps Fused To Ordered Domainsmentioning
confidence: 99%